1998
DOI: 10.1007/bf02461574
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and molecular phylogeny of Tretopileus sphaerophorus, a synnematous hyphomycete with basidiomycetous affinities

Abstract: Tretopileus sphaerophorus, a synnematous hyphomycete with basidiomycetous affinities was newly isolated from the decaying petiole and peduncle of Cocos nucifera collected in Depok, indonesia. The species produced first a bulbil as a propagule on the top of a synnema. After the bulbil had fallen, the synnema proliferated about seven times to produce new bulbils, each time making conspicuous nodes at the upper part. By careful morphological observation, clamp connections were confirmed on the hyphae in the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Morphologically, it produces synnemata with a capitate bulbil-like head proliferating about seven times to yield new bulbils. The species seems to be widely distributed (Okada et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically, it produces synnemata with a capitate bulbil-like head proliferating about seven times to yield new bulbils. The species seems to be widely distributed (Okada et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…& Curtis) Sacc. The morphology and dispersal strategy of Decapitatus recalls somewhat the genus Tretopileus Dodge (1946) that forms "pilei" which fall off and act as propagules (termed bulbils by Okada & al., 1998). In the latter case, the differentiation between the normal basidiome and the anamorph ["gemmifer" (Buller, 1934), "cabecitas" (Wellman, 1950;Salas & Hancock, 1972), "stilboid" structure (Singer, 1951;Seifert, 1985), "cephalosus" (Watling, 1979), or "apokybium" (Cl6menqon, 1997)] is so complete that mycologists have never mixed the two nomenclaturally, or bothered to name a genus for the Stilbunm flavidum anamorph despite the abundance of descriptive vernacular names coined in compensation.…”
Section: Comparative Cases Of Anamorphs and Teleomorphs Based Upon Onmentioning
confidence: 99%
“…& Curtis) S. Hughes & Deighton in Deighton (1960), is quite different, being strongly melanised, and continually regenerating its cephalosus. Okada & al. (1998) reported that Tretopi/eus sphaeromorphus was a basidiomycete, thus far shown to be closer to the Aphyllophorales (using 18S data) than to the agarics, but its pileate form does suggest an agaric relative.…”
Section: New Genusmentioning
confidence: 99%
“…For example, the term "synnema" (i.e. a kind of conidioma) was used for structures producing bulbils in Tretopileus by Okada et al (1998).…”
Section: Morphological Comparison With Other Bulbilliferous Basidiomymentioning
confidence: 99%